Analysis of Managed Care In Primary Health Care Services In Indonesian Health Insurance Management - Elysia Widyadhari; Astri Nurlestari; Femy Dwi Muthashani; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
This study aims analyzes and to evaluate the implementation of the National Health Insurance Program (JKN) in Indonesia, through the perspective of the managed care model. Managed care itself is an approach that combines financing mechanisms and health services in a single integrated system, with a focus on cost efficiency and improving service quality, as implemented by BPJS Kesehatan in Indonesia. This study used a systematic literature review method of 30 scientific articles published between 2016 and 2025. The results of the study indicate that the capitation payment system and INA-CBGs play a role in increasing spending efficiency and expanding access to health services. However, several challenges remain, such as infrastructure gaps, unequal distribution of health workers, and barriers in the referral system. This study also discusses various managed care models such as EPO, IDS, HMO, PPO, and POS, and the relevance of their implementation in the Indonesian context. The findings of the proposed improvement strategies include the use of digital health service technology, strengthening community-based public education, revising more adaptive capitation rates, and improving the monitoring system for service quality and costs. These steps are necessary to support the sustainability and equity of health services throughout Indonesia going forward, along with concrete solutions.